Barriers to LARC Training in OB-GYN Residencies [14OP]. (May 2018) - Evans, Megan L.; Espey, Eve; Ogburn, Tony; Breeze, Janis; Zite, Nikki
Abstract : INTRODUCTION: Widespread provision of LARC relies on adequate provider training. Although LARC education and insertion techniques are required in the OB-GYN residency curriculum, barriers may negatively affect the quality of training. METHODS: This anonymous survey used structured questions about residents' experience with LARC training, including number of LARC insertions. The survey questions were administered electronically in conjunction with the 2016 resident CREOG in-service exam; de-identified data were categorized for analysis by US census regions (Northeast, West, Midwest, South). RESULTS: The response rate for questions about number of LARC insertion was 99%. As of January 2016, 32% of all residents inserted 1–10 IUDs and 31.7% inserted 11–25 IUDs; 39.6% of residents inserted 1–10 contraceptive implants. In total, 8% of chief residents had never inserted an implant and 10% had inserted between 1–10 IUDs Nearly a third of all residents and 40% of Southern residents identified financial barriers, including cost of the device and inadequate insurance coverage, to LARC training. Twenty percent of residents reported institutional policy and 27% reported lack of patient demand as additional barriers. Religious affiliation was reported as a significant barrier only by residents in the Midwest (27%, P <.001) compared to all other residents (6.4%). Residents with low insertion numbers identified institutional religious affiliation as a greater barrier to LARC training than residents with higher insertion rates. CONCLUSION: Residents face a variety of barriers to LARC insertion training and many residents insert fewer than 10 devices during residency.